SURAT PERJANJIAN KONTRAK KERJA DAN PERATURAN REKTOR INSTITUT AGAMA ISLAM NEGERI SURAKARTA NOMOR 51 TAHUN 2014 TENTANG PEGAWAI KONTRAK IAIN SURAKARTA DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA - ARYANI, ARYANI (Dinamika Hukum, 2019)
The study aims to determine the legal position between the Employment Contract Agreement and The Rector of Surakarta State Islamic Institute Regulation Number 51 of 2014 concerning Contract Employees of IAIN Surakarta viewed from the perspective of Law Number 5 of 2014 concerning Civil Servants and their legal consequences. The review of synchronization law uses Stufenbau Theory (Theory of The Pyramid of Law) to find out wether the Rector’c Regulation on Contract Employees of IAIN Surakarta is in accordance with the Civil Servants Law or not. Meanwhile, the theory of the validity of the agreement is used to find out the legal consequences of the IAIN Surakarta’s Working Contract Agreement, as stipulated in the Article 1320 of the Civil Code. This research is descriptive analytical legal (doctrinal) research which describes the contents of the Work Contract and Regulatory Agreement of the Rector of the Surakarta State Islamic Institute Number 51 of 2014 concerning IAIN Contract Employees. Furthermore, it reviews the level off synchronization with the Civil Servants Law using secondary data which is strengthened by primary legal materials in the form of other relevant laws and regulations. The results show that there are many statements in the Work Contract and Regulations of the Rector of the Surakarta State Islamic Institute Number 51 of 2014 concerning Surakarta IAIN Contract Employees which are not in accordance with the regulation of the Civil Sevants Law. Whereas, the Contract of Work Agreement does not meet the legal requirements of the agreement. The inconsistency of the provisions of the Civil Sevants Law brings legal consequences, namely the Rector Regulation of the Surakarta State Islamic Institute Number 51 of 2014 concerning Contract Employees of IAIN Surakarta must be revised. Then, by not fulfilling the legal objective conditions of the agreement, the Letter of Agreement of Work Contract is null and void, deemed that there is considered that was never any agreement . Keywords: Contract Employees, Agreements, Civil Servants Law